2012
DOI: 10.1039/c1ce06027a
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the supramolecular chemistry of pyrazole-4-sulfonate: layered inorganic–organic networks with Zn2+, Cd2+, Ag+, Na+and NH4+, and their use in copper anticorrosion protective films

Abstract: Five compounds based on the versatile pyrazole-4-sulfonate anion (4-SO 3 -pzH ¼ L À ) were synthesized by the reaction of ligand HL with ZnO, CdCO 3 , Ag 2 O, NaOH and NH 3 , respectively. Crystals of Zn(4-SO 3 -pzH) 2 (H 2 O) 2 , Cd(4-SO 3 -pzH) 2 (H 2 O) 2 , Ag(4-SO 3 -pzH), Na(4-SO 3 -pzH)(H 2 O) and NH 4 (4-SO 3 -pzH) were obtained from aqueous solutions upon evaporation, and were characterized by single-crystal X-ray diffraction, IR and NMR spectroscopy, thermogravimetric analysis and copper corrosion inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The cumulative effects of secondary interactions are pivotal to the stability of higher‐dimensional structures, and these interactions provide flexibility to porous frameworks. The synthetic approach often requires the involvement of zero‐, one‐, or two‐dimensional coordination frameworks associated with complementary ligands that offer secondary interactions . Several such reliable synthons that encode well‐defined noncovalent motifs have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The cumulative effects of secondary interactions are pivotal to the stability of higher‐dimensional structures, and these interactions provide flexibility to porous frameworks. The synthetic approach often requires the involvement of zero‐, one‐, or two‐dimensional coordination frameworks associated with complementary ligands that offer secondary interactions . Several such reliable synthons that encode well‐defined noncovalent motifs have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Several anti-corrosion agents have been reported in the literature and MOF compounds emerge as potential candidates. 73,75,[196][197][198][199] This family of materials, typically with high surface areas, wide supramolecular natures and unique topologies, being rich in p-systems and heteroaromatic moieties, should thus attract the interest of industry and society while being employed as corrosion inhibitors. 198 Demadis's research group pioneered the preparation of organic-inorganic hybrid networks with an inhibiting effect on metallic corrosion.…”
mentioning
confidence: 99%
“…200 These authors reported multidimensional MOFs from the self-assembly of phosphonate-or sulfonatebased organic linkers and alkaline, alkaline-earth and transition metal centers. 75,196,197,200,201 In 2008, they reported a series of layered or three-dimensional coordination polymers, generally coined M-HPAA [where HPAA = hydroxyphosphonoacetate; and M = Ma, Ca, Sr and Ba], obtained from hydrothermal synthesis from the adjustment of the pH of the reactive mixtures to 2.7 using NaOH. 75 The resulting M-HPAA materials were formulated as {M[(HPAA)(H 2 O) x ](H 2 O) y } n with x and y determining the amount of metal-coordinated and lattice water.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The impedance spectra of the samples obtained by the EIS test was an important indicator to analyze the corrosion resistance of ZVO materials. 61 In the high frequency region, the Nyquist plots of all samples exhibited a semicircular arc (Figure 7). However, in the intermediate frequency region, the semicircular arc of pure epoxy resin disappeared, demonstrating that the films had been damaged and lost the protective effect.…”
Section: Resultsmentioning
confidence: 94%